The effect of a large anoxic mass fraction and concentrations of nitrate and nitrite in the primary anoxic zone on low f/m filament bulking in nutrient removal activated sludge systems - Musvoto, Eustina V (Department of Civil Engineering, 2023)
Filamentous bulking occurs when filamentous organisms are present in excessive numbers and extend from floes into the bulk solution. They interfere with the compaction and settling of the activated sludge either by producing a very diffuse floe structure or by causing bridging between floes. This results in a sludge with poor settleability i.e., low settling velocity and low solids concentration in the return activated sludge (RAS). In severe cases overflow of the sludge with the effluent occurs. Bulking not only causes these problems in the activated sludge process, but it also causes poor dewaterability of the waste activated sludge. Clearly bulking not only adversely affects the efficiency of the secondary settling tank but also the efficiency of the sludge treatment units at the plant. While controlling or eliminating bulking at plants will certainly be beneficial for sludge handling, by far the most significant impact would be on the activated sludge process itself. It has been estimated that if the sludge settleability could be controlled at Diluted Sludge Volume Indices (DSVI) below 100 me/g, 50 to 100% more wastewater could be treated in existing plants leading to enormous savings (Ekama and Marais, 1986a). This single factor is the principal driving motive behind the research to establish the causes and control of filamentous bulking.